2014
DOI: 10.5171/2014.798969
|View full text |Cite
|
Sign up to set email alerts
|

Distraction Osteogenesis: Evolution and Contemporary Applications in Orthodontics

Abstract: Orthodontic tooth movement is brought about by the biomechanical utilization of the physiological mechanisms for bone remodeling in order to achieve optimal occlusion and thereby maximize the esthetic outcome. Distraction osteogenesis is a biomechanical process of bone tissue formation, where the distraction forces which act between the bone segments effect the biological potential of the bone. Though initially used in long bones, through the past years the technique has undergone significant advancements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The efficacy of DO for the narrowing of an alveolar cleft has been demonstrated (Liou et al, 2000). Liou et al suggested that an alveolar cleft wider than a maxillary canine (8-9 mm) in unilateral or bilateral cleft lip and palate can be minimized or approximated by interdental distraction, creating a controlled fracture in order to minimize the risk for soft tissue and graft failure (Mitsugi et al, 2005; Sakamoto et al, 2011; Cherackal and Thomas, 2014). The disadvantage of the DO approach is the need of a 2-phase surgical technique and additional scar tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of DO for the narrowing of an alveolar cleft has been demonstrated (Liou et al, 2000). Liou et al suggested that an alveolar cleft wider than a maxillary canine (8-9 mm) in unilateral or bilateral cleft lip and palate can be minimized or approximated by interdental distraction, creating a controlled fracture in order to minimize the risk for soft tissue and graft failure (Mitsugi et al, 2005; Sakamoto et al, 2011; Cherackal and Thomas, 2014). The disadvantage of the DO approach is the need of a 2-phase surgical technique and additional scar tissue.…”
Section: Discussionmentioning
confidence: 99%